Formation of viable, but putatively non-culturable (VPNC) cells of beer-spoilage lactobacilli growing in biofilms. (November 2020) - Wang, Zengyan; Chao, Yi; Deng, Yuan; Piao, Meizi; Chen, Tiejun; Xu, Jie; Zhang, Ranran; Zhao, Junfeng; Deng, Yang
Abstract: Bacteria belonging to the genus Lactobacillus are the most commonly-found beer-spoilage microorganisms in breweries. This work compares the ability of biofilm and planktonic cells of beer-spoilage Lactobacillus sp. to enter a viable, but putatively non-culturable (VPNC) state. Planktonic and biofilm cells of five beer-spoilage species of Lactobacillus were incubated at 26 °C in the lager beer with sub-culturing. Both biofilm and planktonic cells could be induced to enter the VPNC state, however, the state-transition time is variable: it took a minimum of 63 days for the biofilm cells to enter the VPNC state, while the time for planktonic cells was 119–217 days. The presence of VPNC cells in non-culturable biofilms was further confirmed by PCR coupled with propidium monoazide pretreatment that amplified genes 16S rDNA and horA . Taken together, this study provides evidence that Lactobacillus biofilm cells can enter the VPNC state at a rate faster than the planktonic cells under stressful conditions of the beer (low pH, high concentrations of hop bitter compounds and ethanol, and limited carbon/nitrogen sources) in the brewing process. Highlights: This is the first report on the formation of VPNC cells in biofilms of beer-spoilage bacteria. Both biofilm and planktonic cells could be induced to form the VPNC state. The entry of biofilm cells to the VPNC state under beer stress was faster than planktonic cells.